La ayuda de estados unidos y de la unión europea a Israel y Egipto: cooperación... ¿al desarrollo? - Prado Lallande, Juan Pablo (Revista Española de Desarrollo y Cooperación, 2023)
Since decades ago, Israel and Egypt have received important aid flows. Nevertheless it´s considerable amount, this aid hasn´t been an effective instrument to foster development in this countries. Between the effects of this situation it’s appropiate to underline that a Mediterranean region of peace and stability hasn’t been enough supported, in disagreement with the aims in this sense expressed by Washington and Brussels.